Pemanfatan Google Maps pada Sistem Penjualan dan Pembelian UMKM Buah Sabar Bekasi - Anshor, Abdulhalim; Rezeki, Fitri; Sunge, Aswan Supriyadi (Lentera Pengabdian, 2024)
This service aims to improve the delivery performance of Buah Sabar MSME products by utilizing Google Maps technology. This activity was motivated by a problem encountered by partners, namely the large number of reseller shops in different areas, making it difficult for employees to detect delivery locations for Buah Sabar MSME products, especially for new workers. Another problem is the partners' low knowledge in the field of information technology, especially Google Maps technology. With assistance and socialization using Google Maps technology, MSME workers can easily find out the location of product delivery from Buah Sabar MSME. This service is carried out by socializing and assisting the use of Google Maps technology by MSME Buah Sabar which is located in Serang Baru District, Bekasi Regency. Delivery of products using Google Maps API technology produces outcomes in the form of improvements in the process of sending MSME Buah Sabar products to reseller shops, Apart from that, this activity can increase the knowledge and quality of workers in the field of information technology, with the implementation of this activity it can encourage and increase sales of Buah Sabar MSME products